Peyssonnelia simulans W.-Van Bosse (Rhodophyta) - A new algal record from St. Martin’s Island, Bangladesh - Aziz, Abdul; Islam, AKM Nurul; Jahan, Asma (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(2): 69, 2004 (December)